A Novel Sustained Anti-Inflammatory Effect of Atorvastatin-Calcium PLGA Nanoparticles: In Vitro Optimization and In Vivo Evaluation - Dalia H. Abdelkader; Ahmed Kh. Abosalha; Mohamed A. Khattab; Basmah N. Aldosari; Alanood S. Almurshedi (MDPI AG, 2021)
Atorvastatin Calcium (At-Ca) has pleiotropic effect as anti-inflammatory drug beside its main antihyperlipidemic action. Our study was conducted to modulate the anti-inflammatory effect of At-Ca to be efficiently sustained for longer time. Single oil-water emulsion solvent evaporation technique was used to fabricate At-Ca into polymeric nanoparticles (NPs). In vitro optimization survey was performed on Poly(lactide-co-glycolide) (PLGA) loaded with At-Ca regrading to particle size, polydispersity index (PDI), zeta potential, percent entrapment efficiency (% EE), surface morphology and in vitro release pattern. In vitro drug-polymers interactions were fully scanned using Fourier-Transform Infrared Spectroscopy (FTIR) and Differential Scanning calorimetry (DSC) proving that the method of fabrication is an optimal strategy maintaining the drug structure with no interaction with polymeric matrix. The optimized formula with particle size (248.2 ± 15.13 nm), PDI (0.126 ± 0.048), zeta potential (−12.41 ± 4.80 mV), % EE (87.63 ± 3.21%), initial burst (39.78 ± 6.74%) and percent cumulative release (83.63 ± 3.71%) was orally administered in Male Sprague-Dawley rats to study the sustained anti-inflammatory effect of At-Ca PLGA NPs after carrageenan induced inflammation. In vivo results demonstrate that AT-Ca NPs has a sustained effect extending for approximately three days. Additionally, the histological examination revealed that the epidermal/dermal layers restore their typical normal cellular alignment with healthy architecture.